Workers’ remittances: A boon to development - Gumisai Mutume (Africa Renewal, 2005)
Every day, thousands of Africans living abroad line up in money-transfer offices to wire home the odd dollar they are able to save. From the US, Saudi Arabia, Germany, Belgium, Switzerland and France — the top sources of remittances to developing countries — some of the money finds its way deep into the rural areas of Africa. There, it may send a child to school, build a house or buy food to sustain those remaining at home.